Topics in Modal Analysis I, Volume 7 Proceedings of the 32nd IMAC, A Conference and Exposition on Structural Dynamics, 2014 - De Clerck, James; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This critical collection examines a range of topics in modal analysis, from experimental techniques to acoustics to biodynamics,  as presented in early findings and case studies from the Proceedings of the 32nd IMAC, A Conference and Exposition on Structural Dynamics, 2014. The collection includes papers in the following general technical research areas:   ·         Experimental Techniques ·         Processing Modal Data ·         Rotating Machinery ·         Acoustics ·         Adaptive Structures ·         Biodynamics ·         Damping.
Infant Brain Response Against Shaking Vibration Using Finite Element Analysis -- Integrity Assessment of Pickup Vehicle Occupants in Rollover Situation Considering Internal ROPS Device: A Numerical Approach -- Rated Life Calculation Potential of Gearbox Model Based Force Estimates -- Electromechanical Impedance Based Crack Detection for a Rotating Machine -- Wind Turbine Gearbox Dynamic Characterization using Operational Modal Analysis -- Mode Classification & Dynamic Analysis of Coupled "Motor-Compressor-Flexible-Foundation" Structures -- Reconstructing Forces From Continuous Connections Using SWAT -- Modal Analysis of Rotating Wind Turbine Using Multiblade Coordinate Transformation and Harmonic Power Spectrum -- Lateral Vibrations in High Speed Over Critical Drive Train Systems -- Vibration Energy Trending and Speed-frequency Transformation in Run-up/ Coast-down Tests -- Vibration Mitigation on Engine Test Stands Using Conventional Analysis Techniques -- Dynamic Modeling and Vibration Analysis of Oilwell Drillstring During Backreaming Operation -- Torsional Damping Identification in Rotating Machinery -- Numerical and Experimental Dynamic System Identification for the Development of Operational Modal Analysis in a Physics-Based Diagnostic/Prognostic Model -- The Influence of Loading Conditions on the Static Coefficient of Friction - A Study on Brake Creep Groan -- Linear Superposition and Modal Participation -- Un-Weighted And Weighted Versions Of The Modal Assurance Criterion (MAC) for Evaluation Of Modal Vector Contamination -- Modal Properties of Rotating Shafts With Order-tuned Absorbers -- Structural Modal Identification Through High Speed Camera Video: Motion Magnification -- Operational Modal Analysis With Photo Images From Low Speed Digital Camera -- Recovery of Mode Shapes From Continuous Scanning Laser Doppler Vibration Data: A Mode Matching Frequency Domain Approach -- A Compact Device for Measuring Rigid-Body Properties Based on Five Unscaled Modes -- Three-Dimensional Modal Parameters of Tire -- Hybrid EMA/OMA Data Collection/Reduction for Improved Modal Characterization -- Numerical and Experimental Determination of Nonlinear Normal Modes of a Circular Perforated Plate -- Experiment of Vibration Isolation Characteristics of a Periodic Curved Beam -- Investigation on Damping of a Host Structure Induced by Attached Cables -- Effect of Structural Damping on Vibrations Transmitted to Road Cyclists -- Statistical Approach for Active Buckling Control With Uncertainty -- An Overview of the Technology, History, and Application of Vibro-Acoustic Coupling -- EMA-BEM-NAH-SEA Path to a Dynamic Filter Model for Violin Radiativity -- Coupled Vibro-Acoustic Model of the Titian Stradivari Violin -- Vibrational Response of Elastic Membranes Coupled to Acoustic Fluids Using a BEM-BEM Formulation -- Parametric Study Of A Continuous Scanning Method Used to Characterize An Acoustic Field.
Keywords: Vibration; Dynamical systems; Dynamics; Aerospace engineering; Astronautics; Mechanics; Mechanics, Applied; Vibration, Dynamical Systems, Control; Aerospace Technology and Astronautics; Solid Mechanics